2023
DOI: 10.3390/inorganics11070308
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Chemistry of [M(NH3)n](XO4)m (M = Transition Metal, X = Mn, Tc or Re, n = 1–6, m = 1–3) Ammine Complexes

Abstract: The preparation of ammine complexes of transition metals having oxidizing anions such as permanganate and perrhenate ions is a great challenge due to possible reactions between ammonia and oxidizing anions during the synthesis of these materials. However, it has an important role in both the development of new oxidants in organic chemistry and especially in the preparation of mixed-metal oxide catalyst precursors and metal alloys for their controlled temperature decomposition reactions. Therefore, in this pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 91 publications
(410 reference statements)
0
1
0
Order By: Relevance
“… A similar nitrile formation reaction was observed only in the oxidation of benzyl alcohol with NH 4 MnO 4 . It is strongly suggested that ammonia formation took place from the urea ligand of compound 5 , which cannot bind strongly to the iron central atom because the strongly bound ammonia in the reaction of tetraamminecopper­(II) permanganate resulted in only a tiny amount of benzonitrile. , …”
Section: Application Of Hexakis(urea)iron(iii) Complexesmentioning
confidence: 99%
“… A similar nitrile formation reaction was observed only in the oxidation of benzyl alcohol with NH 4 MnO 4 . It is strongly suggested that ammonia formation took place from the urea ligand of compound 5 , which cannot bind strongly to the iron central atom because the strongly bound ammonia in the reaction of tetraamminecopper­(II) permanganate resulted in only a tiny amount of benzonitrile. , …”
Section: Application Of Hexakis(urea)iron(iii) Complexesmentioning
confidence: 99%